Impact of using standard and high-resolution exposure modalities of cone-beam computed tomography (CBCT) system for dental implants dimension measurements - Mojdeh Mehdizadeh; Parvaneh Rostamzadeh; Hossein Taheri (Advanced Biomedical Research, 2023)
Background: This study aimed to analyze the effects of standard and high-resolution exposures on the diagnostic accuracy of CBCT in the evaluation of dental implant dimensions. Materials and Methods: A descriptive–analytical study was carried out on 40 dry human mandibles with appropriate ridge quality based on panoramic radiography. CBCT (Soredex, Cranex 3D, Finland) with a large field of view (FOV) and CMOS flat panel detector were used. CBCT with standard and a high resolution was performed in each mandible. Axial images, reconstructed by OnDemand 3D software, were processed to prepare cross-sectional images from the areas marked by gutta-percha, and then measured by a ruler with an accuracy of 0.01 millimeter in the computer. Measurements were recorded by two observers and the obtained data were compared with the real ones. Results: The results showed suitable repeatability in radiologic measurements (r = 0.971), which is indicative of the high reliability of intraobserver measurement. The measurement of width with high-resolution exposure indicated a significant difference with the real condition (P < 0.001); however, this difference was not significant in the case of standard resolution (P > 0.05). Measurement of height with high resolution showed a significant difference with the real condition in the right mandible (P = 0.04) and left mandible (P = 0.05); however, this difference was not significant in standard resolution (P > 0.05). Conclusion: Based on our findings, the standard CBCT resolution modality is suggested for dental implant images due to its higher accuracy than high-resolution methods for diagnosing the implant dimensions.